2021
DOI: 10.5194/esd-12-1015-2021
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of European ecosystems to two compound dry and hot summers in 2018 and 2019

Abstract: Abstract. In 2018 and 2019, central Europe was affected by two consecutive extreme dry and hot summers (DH18 and DH19). The DH18 event had severe impacts on ecosystems and likely affected vegetation activity in the subsequent year, for example through depletion of carbon reserves or damage from drought. Such legacies from drought and heat stress can further increase vegetation susceptibility to additional hazards. Temporally compound extremes such as DH18 and DH19 can, therefore, result in an amplification of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 62 publications
3
82
0
Order By: Relevance
“…Ultimately, if droughts result in widespread species dieback (Mantgem et al ., 2009; Peng et al ., 2011; Mitchell et al ., 2014), they may lead to sustained changes in biodiversity and community composition (Slik, 2004; Nepstad et al ., 2007; Anderegg et al ., 2013), altering land–atmosphere feedbacks (Swann et al ., 2018) on seasonal to decadal timescales. To develop a predictive framework and better understand the impacts and implications of changes in the timing, severity and spatial extent of climatic extremes, we need to combine insights across scales (McDowell et al ., 2016), including field ecology (Rowland et al ., 2015), remote sensing (Bastos et al ., 2021), modelling and climate science (Williams et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, if droughts result in widespread species dieback (Mantgem et al ., 2009; Peng et al ., 2011; Mitchell et al ., 2014), they may lead to sustained changes in biodiversity and community composition (Slik, 2004; Nepstad et al ., 2007; Anderegg et al ., 2013), altering land–atmosphere feedbacks (Swann et al ., 2018) on seasonal to decadal timescales. To develop a predictive framework and better understand the impacts and implications of changes in the timing, severity and spatial extent of climatic extremes, we need to combine insights across scales (McDowell et al ., 2016), including field ecology (Rowland et al ., 2015), remote sensing (Bastos et al ., 2021), modelling and climate science (Williams et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Bastos et al . (2021) concluded that amplified evapotranspiration during the hot spring of 2018 in Europe was related to dry and hot conditions in summer that year. These lagged relationships and their simulation in the RCMs are beyond the scope of the present study but deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Della-Marta et al (2007) and Russo et al (2019) showed that hot summers in the Mediterranean tend to be preconditioned by dry springs and, in addition, dry springs over the Mediterranean also contribute to the development of extreme heat in continental Europe (Zampieri et al, 2009). Bastos et al (2021) concluded that amplified evapotranspiration during the hot spring of 2018 in Europe was related to dry and hot conditions in summer that year. These lagged relationships and their simulation in the RCMs are beyond the scope of the present study but deserve further investigation.…”
Section: Role Of Models' Spatial Resolution Driving Data and Temporal...mentioning
confidence: 99%
“…Drought legacy effects are known to reduce tree-level growth (Anderegg et al, 2015), and, more broadly, resilience (Bose et al, 2020). Thus, the previous drought-induced low N DV I event could be a sign of reduced tree vigor and higher susceptibility for a following drought, as detected, e.g., in 2019 (Schuldt et al, 2020;Bastos et al, 2021). Moreover, forests potentially acclimate to increased drought stress, which might also lead to reduced leaf area and productivity (Gessler et al, 2020).…”
Section: Drought Legacy Effects and Event Recoverymentioning
confidence: 99%